Implementation of a sound research center for the performing arts: Arquivos Sonoros de Teatro project (Urdimento: Revista de Estudos em Artes Cênicas, 2025)
This article addresses the implementation of the Theater Sound Archives project (University of São Paulo/São Paulo Research Foundation), which navigates the challenges of a research field that is relatively nascent globally (Mervant-Roux, 2023). We present an overview of international policies and projects concerning the preservation of sound archives and describe the Brazilian context and the Tunica Teixeira Collection, the project's inaugural archive. Consequently, we reaffirm the necessity of strengthening sound archives as a vital source for theater research and documentation, as well as the urgent need for investment to ensure the preservation of theatrical sound memory and its accessibility to future generations of researchers and creators.
Keywords: sound archives; theater archives; preservation; digital preservation; stage sound